Birth defects: Risk factors and consequences - Oliveira, Camila Ive Ferreira [UNESP]; Fett-Conte, Agnes Cristina (IOS Press, 2013)
Birth defects (BDs) or congenital anomalies include all structural and functional alterations in embryonic or fetal development resulting from genetic, environmental or unknown causes, which result in physical and/or mental impairment. BDs occur in about 3% of newborn babies and in most cases of pregnancy loss. BDs are a very complex and heterogeneous group of single or multiple changes that, in most cases, are of unknown etiology. Among the risk factors are advanced maternal and paternal ages, parental consanguinity, teratogenic agents such as infectious agents and drugs, and poor nutrition, in particular folic acid deficiency. One of the consequences of these defects is the high death rate within the first year of life. Information on BDs is becoming increasingly more important throughout the world so that preventive measures can be taken. Knowledge of BDs enables the development of therapeutic and preventive strategies besides adequate genetic counseling. © 2013 - IOS Press and the authors.
Keywords: Chromosomal abnormalities; Congenital anomalies; Congenital malformation